2022
DOI: 10.1002/lio2.841
|View full text |Cite
|
Sign up to set email alerts
|

Effect of desmopressin on bleeding during endoscopic sinus surgery: A randomized clinical trial

Abstract: Background This study aimed to evaluate the effect of local nasal desmopressin premedication on blood loss and the quality of surgical field in Functional Endoscopic Sinus Surgery (FESS). Material and methods In a randomized clinical trial, patients referred for FESS to treat their bilateral chronic rhinosinusitis were recruited. The participants were adults (≥18 years). They were randomly assigned (1:1:1) to receive low‐dose (20 μg) or high‐dose (40 μg) intranasal desmopressin (DDAVP) or placebo 60 min before… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 30 publications
(58 reference statements)
1
9
0
1
Order By: Relevance
“…Although some have recommended this technique as an effective way of reducing blood loss during surgery, [2][3][4][11][12][13] we could not find any significant difference in bleeding between the study and control sides ( p = 0.49), similar to the results of Kumar et al 14 and Valdes et al 1 In a review paper by Shamil et al, in 2017, of seven articles, only two demonstrated a decrease in blood volume in the surgical field in the study group. 15 In contrast, Hwang and colleagues reviewed five articles, which were in favour of this method; additionally, the authors declared that the concentration of 1:80 000 adrenaline solution had a better result in comparison to 1:100 000.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Although some have recommended this technique as an effective way of reducing blood loss during surgery, [2][3][4][11][12][13] we could not find any significant difference in bleeding between the study and control sides ( p = 0.49), similar to the results of Kumar et al 14 and Valdes et al 1 In a review paper by Shamil et al, in 2017, of seven articles, only two demonstrated a decrease in blood volume in the surgical field in the study group. 15 In contrast, Hwang and colleagues reviewed five articles, which were in favour of this method; additionally, the authors declared that the concentration of 1:80 000 adrenaline solution had a better result in comparison to 1:100 000.…”
Section: Discussionsupporting
confidence: 82%
“…Correction of coagulopathies, avoidance of predisposing medications in the pre-operative period, proper patient positioning, anaesthetic protocol, topical vasoconstriction, and some drugs like beta-blockers, tranexamic acid and desmopressin, are some of the preventive measures used to decrease blood in the surgical field. 2,3 There are limitations of beta-blocker usage in some patients (e.g. those with asthma); in addition, reports of blindness after the intranasal injection of vasoconstrictors, and limited accessibility of systemic and topical haemostatic agents, are encountered in some instances.…”
Section: Introductionmentioning
confidence: 99%
“…In a different study done by Akbarpour et al [ 18 ], a significant link was found between the type of surgery and the amount of blood loss. However, it is important to note that a mean difference of only 0.4 ml was found between the low-dose desmopressin group and the control group [ 18 ]. But when compared to the high-dose DDAVP group, the controls saw a 29.6 ml drop in bleeding during surgery.…”
Section: Reviewmentioning
confidence: 99%
“…But when compared to the high-dose DDAVP group, the controls saw a 29.6 ml drop in bleeding during surgery. The size of the resulting effect is a very important factor [ 18 ]. At both the first and second time points, the link between the type of surgery and the quality of the operating field was seen.…”
Section: Reviewmentioning
confidence: 99%
See 1 more Smart Citation